A serum metabolomics study on the intervention of nonalcoholic fatty liver disease by equicaloric low-carbohydrate high-protein diet combined with aerobic exercise - LI Meiying (Editorial Department of Journal of Clinical Hepatology, 2021)
ObjectiveTo collect the serum samples of patients with nonalcoholic fatty liver disease (NAFLD), and to investigate the changes in serum metabolic biomarkers before and after lifestyle intervention. MethodsA total of 23 patients who were diagnosed with NAFLD in Department of Gastroenterology and Inpatient Department, Putuo District Central Hospital of Shanghai, from January 2019 to January 2020 were enrolled, and all patients received the intervention with aerobic exercise and equicaloric low-carbohydrate high-protein diet. A total of 13 healthy volunteers who underwent physical examination in Physical Examination Center were enrolled as control group. For the patients with NAFLD, basic information was collected before and after intervention, blood samples were collected twice to measure liver function, blood glucose, and blood lipids, and part of serum was used for serum metabolomics analysis. The serum samples were analyzed by ultra-performance liquid chromatography/tandem high-resolution mass spectrometry. The data collected were processed in Compound Discover, and then principal component analysis (PCA) and orthogonal partial least squares discriminant analysis were used to establish the profile of differentially expressed blood metabolites between patients and healthy people and perform the enrichment analysis of differentially expressed metabolic pathways. The independent samples t-test was used for comparison of normally distributed continuous data between two groups, and the Wilcoxon non-parametric test was used for comparison of non-normally distributed continuous data between two groups. ResultsAfter lifestyle intervention, the patients had significant reductions in body mass index (P＜0.01), body weight (P＜0.01), and serum biochemical parameters alkaline phosphatase, albumin, gamma-glutamyl transpeptidase, and alanine aminotransferase (all P＜0.05), as well as a significant reduction in total protein (P＜0.01), while there were no significant improvements in cholinesterase, aspartate aminotransferase, and glucose. As for the four items for blood lipids, there was a significant reduction in triglyceride (P＜001), while there were no significant improvements in high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and total cholesterol. The metabolomics analysis showed that 33 serum metabolites changed significantly after lifestyle intervention. In addition, PCA results showed that after intervention, the level of metabolites in patients tended to be normal. The signaling pathway analysis showed that exercise and diet mainly affected the pathways of bile acid, unsaturated fatty acid synthesis, and phenylalanine metabolism. ConclusionLifestyle intervention can achieve varying degrees of reduction in the body weight of patients with NAFLD, improve serum biochemical parameters, and regulate the abnormal metabolic pathway in patients with NAFLD, which has important clinical value and significance for guiding clinicians to formulate reasonable diet and exercise strategies for patients with NAFLD and prevent the progression of NAFLD.